FOURTH-GENERATION HUMAN RIGHTS AND THE VIOLATION OF THE CONCEPT OF PRIVACY - Nuredin, Abdulmecit (International Scientific Journal Vision, 2023)
Internet drove the world in the path of advancement. In the present situation, the regular lives of individuals are intermingled with the uses of the internet. Therefore, the lack of accessibility can put the individual in the backward stage of life. Therefore, the accessibility of the internet can be considered a significant human right in the fourth generation. however, the use of the internet has even some negative sides. Since the use of the internet is easy and rapid, it has become an easy podium to intrude into the private lives of others. maintaining privacy is also a human right. therefore, in a time where both the accessibility of the internet and the maintenance of privacy are important, the question lies in the relationship. Therefore, the aim of the paper is eventually is to discuss the fourth-generation human rights and the violation of the concept of privacy.